Decision Support System for Determined Recomendations Lecturer Teaching Handbook using Fuzzy - Usman Rizal; Fenty Ariani (International Conference on Engineering and Technology Development (ICETD), 2014)
Textbook or teaching manuals book have many kind of such material and content of the same though. The textbook on the market make the teachers confused in choosing an appropriate textbook, it make the teachers sometimes choose the wrong textbook and the suitability the content of the material it’s not in the same content. In the fact the content from a same book can be different. Textbook is one factor that can influence teachers to choose the book for refrency.By using fuzzy in this application, the recommendations value of teaching guidebook based on the results of the calculation in the settlement with the fuzzy and the discovery of the book can be recommended after the process of calculating the value of the matrix preference normalization and order exist on the object of research.